曲线求存的本土文化 ：探析新加坡歌台的发展策略 = The living curve of local culture : an analysis of development strategies of Getai in Singapore - Ong, Wee Xiang (2016)
新加坡歌台，一般上给人的印象是娱乐性质的演出，以及农历七月的酬神表演。2012 年，歌台却被《艺术与文化策略检讨委员会报告书》肯定为新加坡的艺术和文化，有了根本性的变化。本研究发现，新加坡歌台发展充满着危机，2000 年后更面临了内外夹攻。内部危机包括歌台制作的困境与博物馆化的危险。外部危机则有演出空地的消失以及人们不谙方言的问题。值得庆幸的是，新加坡歌台也相应地采取了三管齐下的策略，使其能在重重危机中起死回生，生生不息。这三大措施分别是家族式歌台的本土化，传宗接代的童星制度，以及多向全球化网络的展开。虽然未能完全地消解所面临的所有危机，这些策略却让新加坡歌台在危机中能够塑造自己的特色，赢得了众人的支持与国家的肯定。In Singapore, getai has long been regarded as a form of entertainment show, or a performance connoted to Hungry Ghost Festival. However, in the year of 2012, getai was distinguished as Singapore’s arts and culture by “The Report of the Arts and Culture Strategic Review”, and this marks a significant milestone to it. This paper finds out that the development of getai is facing dangers and challenges, especially in the 21st century. It struggles with inner and outer problems. The inner problems include the production of getai as well as the Musuemification of getai, while the outer ones comprise the diminishing available lands in Singapore, and waving dialects. Getai has also adopted three strategies to tackle on these problems. They are localization of getai groups, the child apprenticeship as well as globalized networks. Although these three strategies may not solve the problems entirely, they have essentially highlighted the essence of getai, whereby winning the support of its audience and the acknowledgment by the nation.